TRADE IN THE CONTEXT OF THE EMERGENCE OF A MARKET ECONOMY - Erdonov Muhammadamin Erdon o‘g‘li; Tog’ayev Mirzobek Botir o’g’li (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Abstract: This article examines the essence and features of trade in the conditions of the emergence of a market economy. In the context of a changing economic environment, we analyze the role of trade in the development of market relations, its impact on economic growth and development of the country. The article also examines the challenges and opportunities faced by trading enterprises during the formation of a market economy, and also proposes strategies for successful operation and development in the new conditions.